Economic dynamics of tissue cultured strawberry (Fragaria× ananassa) under the influence of integrated plant nutrients in humid sub tropical hills of North Eastern India - HAZARIKA, T K; RALTE, ZOTHANKIMA; NAUTIYAL, B P (The Indian Journal of Agricultural Sciences, 2016)
Satisfactory and sustainable level of agricultural production can be achieved by combined application of inorganic fertilizers with organic manures, bio-fertilizers, bio-regulators and vermicompost. A field experiment was conducted during 2010-12 at experimental farm, Department of Horticulture, Aromatic and Medicinal Plants, Mizoram University, Aizawl, India, to find out the profitability of tissue cultured strawberry (Fragaria × ananassa Duch.) (cv. Festival) cultivation by using various integrated plant nutrient system (IPNS) combining inorganic fertilizers with organic manures, bio-fertilizers and bio-regulators. The response of IPNS on economics of strawberry indicated that the overall cost of cultivation as well as economics of strawberry production was significantly influenced by integration of various components. Among the different treatments, the highest expenditure of Rupees 2 077 576.83/ha was incurred in 100% RDF + vermicompost as against the lowest in control. With respect to the income, the highest net income of Rupees 7 298 119.27/ha was obtained in 75 % RDF + vermicompost + Azospirillum + PSB + 50 ppm GA3+50 ppm BA. The same treatment also recorded the highest cost benefit ratio of 1: 3.51.